Stream model of the Amazon River basin derived from 1 arcsecond SRTM digital elevation model - Alexander A Wheatley (PANGAEA, 2019)
A model of streams with Strahler order 4 or higher for the Amazon River watershed area, derived from the SRTM 1 arcsecond product. Areas where the 1 arcsecond data product is unavailable were filled with the 3 arcsecond product, resampled to 1 arcsecond; streams segments overlapping these areas are not included. Four products are provided: 1) The final digital elevation model, with voids filled from the 3 arcsecond SRTM product, and sinks filled with the ESRI ArcGIS fill tool. 2) The stream model derived from this DEM, with lengths and flow directions computed in the ESRI South American Lambert Conformal Conic projection. 3) All watersheds of Strahler order 9, 10, 11 or 12 (the order 12 watershed being the full Amazon River watershed), with area computed in the ESRI South American Albers Equal Area Conic projection. 4) Location of voids in the 1 arcsecond SRTM data product.